The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5935/abc.20130145
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient Knowledge of Cardiac Rehabilitation: Brazil vs Canada

Abstract: BackgroundMuch of the relationship between health status and knowledge about health and disease can be attributed to the combined effects of disparate health-related behavior, environmental conditions, and socioeconomic structures as well as contact with and delivery of health care. ObjectiveThe aim of this study was to describe and compare knowledge of patients with coronary artery disease (CAD) enrolled in cardiac rehabilitation (CR) programs in Brazil and Canada about CAD-related factors. MethodsTwo samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
1
6
1
1
Order By: Relevance
“…In contrast to housewives and the difference was statistically significant. In accordance other study conducted by (Ghisi et al, 2013) among atrial fibrillation patients reported significant correlation between occupation and knowledge.…”
Section: (Table 4)supporting
confidence: 89%
“…In contrast to housewives and the difference was statistically significant. In accordance other study conducted by (Ghisi et al, 2013) among atrial fibrillation patients reported significant correlation between occupation and knowledge.…”
Section: (Table 4)supporting
confidence: 89%
“…In this regard, these proposals should be grounded in simple models, with high population coverage, since less educated patients are the ones who would benefit most from educational interventions. 22…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the 19-item Coronary Artery Disease Education Questionnaire (CADE-Q) was previously developed and psychometrically-validated to assess CR patients' knowledge about CAD [15][16][17]. It is one of the very few available tools to measure CAD patient knowledge in the CR context that is psychometrically-validated [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%